The Role of the School Principal as a Manager in Improving the Quality of Learning Through Learning Communities at SD Negeri 1 Kalipang, Rembang Regency - Sugiharti Sugiharti; Yovitha Yuliejantiningsih; Muhammad Prayito (Journal of Educational Sciences, 2026)
This study examines the role of the principal as a manager in improving the quality of learning through learning communities at SD Negeri 1 Kalipang. The research aims to understand how effective school leadership can enhance teaching quality by organizing collaborative learning environments for teachers. The findings suggest that the principal's involvement in planning, organizing resources, and motivating teachers has significantly contributed to the success of the learning community program. By engaging teachers in collaborative activities and fostering a culture of continuous professional development, the school has enhanced both teaching competencies and student engagement. Despite challenges such as a limited number of certified teachers in certain subjects, the school has been successful in overcoming these obstacles through training and resource optimization. This study highlights the importance of a principal’s leadership in fostering a supportive learning community, which ultimately improves educational outcomes. The results provide valuable insights for other schools aiming to implement similar programs to enhance learning quality and teacher development.